BRAZILIAN SOCCER: HOW TO REACH THE SUCCESS BEYOND THE SOCCER FIELD. (Fiep Bulletin - online, 2014)
The current work has as a main goal to show to the soccer clubs' sports managers, the principle orientations of sport administration, their new tendencies and how to turn the administration more effective.Considering that a great number of Physical Education professionals are part of the administrative team of a sporty institution and that your academic formation does not foresee in the curriculum a specific discipline for such, this work has a mission to show the elements that will turn it informed about the topic and the world's perspectives.  Topics like sport marketing; mark and licensing will be boarded as products of a sport administration, where the manager's objectives are to control the variables of these themes for a good usage and the benefits of the institution.The Brazilian market's opportunities are explored in the text considering the world's tendencies, comparing to what is already being made in Brazil and showing that the increase of perspectives in the cited markets is gigantic.As the final part of the text, the planning arises as instruments make the implantation of the goals easier, control the results and to make possible future plans, creating thus a facilitator mechanism for the new enterprises implantation.
Keywords: Sport administration; Sport Management; Soccer